2014
DOI: 10.1523/jneurosci.0747-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Social Interaction Rescues Memory Deficit in an Animal Model of Alzheimer's Disease by Increasing BDNF-Dependent Hippocampal Neurogenesis

Abstract: It has been recognized that the risk of cognitive decline during aging can be reduced if one maintains strong social connections, yet the neural events underlying this beneficial effect have not been rigorously studied. Here, we show that amyloid precursor protein (APP) and presenilin 1 (PS1) double-transgenic (APP/PS1) mice demonstrate improvement in memory after they are cohoused with wild-type mice. The improvement was associated with increased protein and mRNA levels of BDNF in the hippocampus. Concomitant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
83
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(92 citation statements)
references
References 48 publications
(1 reference statement)
8
83
0
Order By: Relevance
“…2, the hippocampal and cortical BDNF expression in APP/PS1 mice were significantly less than that in WT control mice (n=5, p<0.01 vs. WT+Vehicle), consistent with previous findings. 28,39,40) In line with the behavioral data, chronic donepezil administration significantly enhanced the expression of hippocampal and cortical BDNF in APP/PS1 mice (n=5, p<0.01 vs. APP/PS1+Vehicle). Donepezil treatment did not affect the BDNF expression in WT control mice (n=5).…”
Section: Chronic Donepezil Administration Restores the Memory Impairmsupporting
confidence: 73%
“…2, the hippocampal and cortical BDNF expression in APP/PS1 mice were significantly less than that in WT control mice (n=5, p<0.01 vs. WT+Vehicle), consistent with previous findings. 28,39,40) In line with the behavioral data, chronic donepezil administration significantly enhanced the expression of hippocampal and cortical BDNF in APP/PS1 mice (n=5, p<0.01 vs. APP/PS1+Vehicle). Donepezil treatment did not affect the BDNF expression in WT control mice (n=5).…”
Section: Chronic Donepezil Administration Restores the Memory Impairmsupporting
confidence: 73%
“…Previous studies reported that 6-monthold APP/PS1 mice experience mild decline in social interaction function, exhibiting no preference to stay in the empty chamber versus the one having unfamiliar mouse Hsiao et al 2014). The present study revealed that 24-month-old APP/PS1 mice spent more time in the empty chamber than with the unfamiliar partner, indicating the occurrence of social interaction impairment.…”
Section: Discussionmentioning
confidence: 97%
“…Evidence has suggested that dysfunction of BDNF is a possible contributor to the pathology and symptoms of AD (Tapia-Arancibia et al 2008). BDNF is found to be decreased in APP/PS1 mice even in the early stages of AD-like pathology (Peng et al 2009;Hsiao et al 2014). Apart from BDNF, other neurotrophic factors, such as nerve growth factor (NGF) and glial cell-derived neurotrophic factor (GDNF), are also involved in normal aging and AD (Allen et al 2013;Budni et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, factors that protect the heart can also protect the brain and reduce the risk of developing AD and; physical activity is considered as the central of these factors [42][43][44]. In addition, it is well known that consuming a healthy heart diet is associated with reduction of AD and dementia [45][46][47][48].…”
Section: Resultsmentioning
confidence: 99%